Application of anthropometric measurements analysis for stature in human vertebral column: A systematic review - Chee Leong Choong; Aspalilah Alias; Razif Abas; Yuan Seng Wu; Ja Young Shin; Quan Fu Gan; Khin Myo Thu; Ker Woon Choy (Elsevier Ltd, 2024)
Indexed by Scopus